1994
DOI: 10.1109/59.336135
|View full text |Cite
|
Sign up to set email alerts
|

Real-time EMTP-based transients simulation

Abstract: A computer program has been written for the simulation of power system transients in real time. The program is based on EMTP models and solution techniques optimized for maximum performance in superscalar computer architectures. Timings ranging from 38 to 107 ps have been obtained for systems from 18 to 30 nodes using an JBM RISC System/6000 Model 560 workstation. These timings are considered adequate for real-time testing of protective relaying equipment. The program is compatible with existing E M " data cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…After almost a decade now, various research groups have been able to achieve real-time performance [9], [10], [11], [12]. The real-time research group of the University of British Columbia has been continuously advancing the concept of a full-size real-time power system simulator, which eventually resulted in the OVNI [13] power system simulator.…”
Section: Real-time Power System Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…After almost a decade now, various research groups have been able to achieve real-time performance [9], [10], [11], [12]. The real-time research group of the University of British Columbia has been continuously advancing the concept of a full-size real-time power system simulator, which eventually resulted in the OVNI [13] power system simulator.…”
Section: Real-time Power System Simulationmentioning
confidence: 99%
“…There are mainly five well-known research groups working in the field of real-time power system simulators using different approaches. Electricité de France (EDF) and Hydro Que- Stemming from this work several other research projects originated at UBC, examples of which are the RTNS extensions and hardware implementation for testing relays [16] developed by Jesús Calviño; the Multi-layered tearing solution software [10]; and the Real-Time Distributed Network Simulator, developed by J. Hollman (RTDNS) [17]. See Fig.1.1.…”
Section: Real-time Power System Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, as information does not propagate faster than the speed of light, if the line travel time is longer than one time-step, effectively the two sides of the TL are computationally decoupled and can be executed in parallel on the GPU. This fact is used in many real-time simulators such as [25], [26]. Also, calculations in the modal domain themselves can be performed in parallel.…”
Section: E Gpu-based Implementation Of Other Power System Componentsmentioning
confidence: 99%
“…ATP enables the simulation of electromagnetic transient phenomena on the basis of sophisticated models of transmission lines, transformers, electric machinery, etc., as well as the components of circuits and elements that control the switches and triggers of thyristors [10,11]. Studies conducted in the 1990s that continued until 2010 [12][13][14] reported the development of real-time simulators based on EMTP [15,16].…”
Section: Introductionmentioning
confidence: 99%